Imaging in gynecological disease (21): clinical and ultrasound characteristics of accessory cavitated uterine malformations. (13th April 2021) - Naftalin, J.; Bean, E.; Saridogan, E.; Barton‐Smith, P.; Arora, R.; Jurkovic, D.
Abstract: Objective: To describe the clinical and ultrasound characteristics of accessory cavitated uterine malformations (ACUMs). Methods: This was a single‐center observational study of consecutive patients diagnosed with an ACUM, who had undergone an ultrasound examination by an experienced ultrasound examiner between January 2013 and May 2019, identified retrospectively from medical records. ACUM was diagnosed when a cavitated lesion with a myometrial mantle and echogenic contents was seen within the anterolateral wall of the myometrium beneath the insertion of the round ligament. In all women, presenting symptoms and clinical history were recorded along with detailed descriptions of the lesions and any concomitant pelvic abnormalities. Results: Twenty patients diagnosed with an ACUM were identified. Median age was 29.2 (interquartile range, 25.0–35.8) years. None of the women was premenarchal or postmenopausal. All of the women reported painful periods or pelvic pain and none of them reported subfertility. Twelve of the ACUMs were in the right anterolateral myometrium and eight were in the left anterolateral myometrium. Both a myometrial mantle and a fluid‐filled cavity were considered to be defining features on ultrasound. The fluid contained within the cavity was either echogenic with a ground‐glass appearance or hyperechoic. All of the lesions were spherical in shape. The Doppler flow seen in the outer rim was not markedly different from that of the surrounding myometrium, and the content of the cavity was avascular on Doppler examination. The mean outer cavity diameter of the ACUMs was 22.8 (95% CI, 20.9–24.8) mm and the mean internal cavity diameter was 14.1 (95% CI, 12.2–16.1) mm. Four women opted for transvaginal ultrasound‐guided alcohol sclerotherapy. Surgical excision was carried out in eight cases, and the diagnosis was confirmed on histopathological examination in all of them. Conclusions: ACUMs are a uterine abnormality with a distinct ultrasound appearance, which are associated with dysmenorrhea and chronic pelvic pain. Knowledge of their typical appearance on ultrasound could facilitate early detection and treatment. There are several treatment options for ACUM, ranging from simple analgesia to complete excision. Further prospective and longitudinal studies are required to study the prevalence and natural history of this condition. © 2020 International Society of Ultrasound in Obstetrics and Gynecology